Responsible librarianship : library policies for unreliable systems - Bade, David W. (Library Juice Press, 2007)
These papers examine library policies and organizational structures in light of the literature of ergonomics, high reliability organizations, joint cognitive systems and integrational linguistics. Bade argues that many policies and structures have been designed and implemented on the basis of assumptions about technical possibilities, ignoring entirely the political dimensions of local determination of goals and purposes as well as the lessons from ergonomics, such as the recognition that people are the primary agents of reliability in all technical systems. Because libraries are understood to be loci of human interaction and communication rather than purely technical systems at the disposal of an abstract user, Bade insists on looking at problems of meaning and communication in the construction and use of the library catalog. Looking at various policies for metadata creation and the results of those policies forces the question: is there a responsible human being behind the library web site and catalog, or have we abandoned the responsibilities of thinking and judgment in favor of procedures, algorithms and machines?